Quantum conductance of a single magnetic atom: An ab initio study - SANVITO, STEFANO; RUNGGER, IVAN (My University, 2010)
Our ab initio study explains recent puzzling experiments on the conductance of a single Co adatom depos- ited either on Cu 111 or on ferromagnetic Co islands and contacted with both magnetic and nonmagnetic electrodes N. Neel, J. Kroger, and R. Berndt, Phys. Rev. Lett. 102 , 086805 2009 . We provide clear evidence that the conductance of a single atomic junction in the contact regime is close to G 0 / 2 G 0 is the quantum of conductance for ferromagnetic electrodes and to G 0 for nonmagnetic ones. Spin-dependent calculations reveal that a conductance of G 0 / 2 originates from a combination of partially open majority and minority channels. The bonding between the Co adatom and the Co island reduces significantly the contribution of the minority d electrons to the conductance, leading to the observation of half-integer conductance
PUBLISHED
Keywords: Physics